Synthesis, characterization, experimental design and process analysis of heavy metals adsorption on a wheat straw based amidoximated bioadsorbent - Mostafa Sheikhmali; Elham Jalilnejad; Reza Rafiee (Scientific Reports)
Abstract In this research, 3-(trimethoxysilyl)propyl methacrylate (MPS) silane agent was applied to modify the extracted wheat straw (WS) cellulose as a natural biopolymer. Polyacrylonitrile (PAN) was attached to the MPS-modified WS (MPS-WS) via in-situ polymerization to form PAN-WS biocomposite. AO-WS amidoximated biocomposite adsorbent was synthesized through amidoxime reaction and the effects of different parameters including agitation speed, metal ion concentration, and adsorbent dosage on its efficiency of Pb(II) removal were investigated using the Taguchi experimental design method. The adsorbent was characterized using FE-SEM, FTIR, XRD, and TGA. The FTIR results confirmed that the alkaline treatment removed the hemicellulose and lignin groups and that the silane agent successfully bonded to the WS cellulose. The thermal stability of WS was enhanced by the MPS-WS composite due to the attachment of acrylonitrile polymer chains. The ANOVA results indicated that increasing the adsorbent dosage and decreasing the pollutant’s initial concentration significantly improved the adsorption efficiency. The optimal conditions (an agitation speed = 400 rpm, C0 = 60 mg/L, an adsorbent amount = 0.1 g) yielded maximum adsorption capacity of 22.26 mg/g for the AO-WS bioadsorbent. The kinetic and isotherm studies revealed that the pseudo-second-order kinetic model and the Dubinin-Radushkevich isotherm fit the experimental data best.